2010
DOI: 10.1177/0269881110372548
|View full text |Cite
|
Sign up to set email alerts
|

Topiramate augmentation of clozapine in schizophrenia: a double-blind, placebo-controlled study

Abstract: The persistence of psychotic, affective, cognitive, and psychosocial symptoms despite medications is commonly observed in schizophrenic patients. The present study was a 24-week double-blind, randomized, placebo-controlled trial aimed to explore the efficacy of topiramate add-on pharmacotherapy on clinical symptomatology and cognitive functioning in a sample of treatment-resistant schizophrenic patients receiving clozapine. After clinical and cognitive assessments were randomly allocated to receive either up t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(46 citation statements)
references
References 55 publications
(58 reference statements)
1
43
0
1
Order By: Relevance
“…Similar benefit was also seen with duloxetine in a study by this same group[9], but not with topiramate. [10] There remains no clear recommendation for how to augment clozapine or what other strategies to employ when an individual does not tolerate or respond meaningfully to clozapine.…”
Section: Schizophrenia That Is Unresponsive To Treatmentmentioning
confidence: 99%
“…Similar benefit was also seen with duloxetine in a study by this same group[9], but not with topiramate. [10] There remains no clear recommendation for how to augment clozapine or what other strategies to employ when an individual does not tolerate or respond meaningfully to clozapine.…”
Section: Schizophrenia That Is Unresponsive To Treatmentmentioning
confidence: 99%
“…Of note, 19 patients received topiramate and 24 placebo: the Winsconsin Card Test scores of the topiramate group did not significantly change compared to placebo [43]. These results have not been confirmed by further studies.…”
Section: Topiramatementioning
confidence: 83%
“…In a 24-week double-blind, randomized, placebo-controlled trial adjunctive topiramate (up to 200 mg/day) to clozapine even worsened cognitive functioning of 43 treatment-resistant schizophrenia patients [43]. Of note, 19 patients received topiramate and 24 placebo: the Winsconsin Card Test scores of the topiramate group did not significantly change compared to placebo [43].…”
Section: Topiramatementioning
confidence: 97%
“…Several studies suggested topiramate's efficacy for treatment-resistant positive and negative symptoms [96,97], in particular in patients with partial response to CLZ. However, significant superiority over placebo could not be demonstrated in a recent meta-analysis [87], and worsening of cognitive abilities might be a potential side effect [98,99]. Some investigators also intended to reduce appetite and body weight in schizophrenia [96][97][98][99] or bipolar disorder [100].…”
Section: Mk-801 Olz and Other Fgas And Sgasmentioning
confidence: 99%
“…However, significant superiority over placebo could not be demonstrated in a recent meta-analysis [87], and worsening of cognitive abilities might be a potential side effect [98,99]. Some investigators also intended to reduce appetite and body weight in schizophrenia [96][97][98][99] or bipolar disorder [100]. In line with a recent review on the benefits and the risks of topiramate treatment in schizophrenia [101], further research in patients in early disease stages seems necessary.…”
Section: Mk-801 Olz and Other Fgas And Sgasmentioning
confidence: 99%